2009
DOI: 10.1088/0031-9155/54/21/019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced diffuse optical tomography (DCE-DOT): experimental validation with a dynamic phantom

Abstract: Dynamic contrast-enhanced diffuse optical tomography (DCE-DOT) can provide spatially resolved enhancement kinetics of an optical contrast agent. We undertook a systematic phantom study to evaluate the effects of the geometrical parameters such as the depth and size of the inclusion as well as the optical parameters of the background on the recovered enhancement kinetics of the most commonly used optical contrast agent, indocyanine green (ICG). For this purpose a computer-controlled dynamic phantom was construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We used a combined MR-DOT system that has previously been described in detail (2123). This system used a series of eight source fibers to deliver light from laser diodes modulated at 100MHz to the animal being imaged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a combined MR-DOT system that has previously been described in detail (2123). This system used a series of eight source fibers to deliver light from laser diodes modulated at 100MHz to the animal being imaged.…”
Section: Methodsmentioning
confidence: 99%
“…However, in vivo studies in the literature showed that following the administration, the ICG concentration reached to its peak in nearly one minute (10, 17). To be able to monitor the enhancement kinetics of ICG, we recently increased the time resolution of our DOT system to 16 seconds using a heterodyne detection technique (23). The new version of the system recorded the output signals of the PMTs simultaneously using NI 4472 8-channel DAQ system after the down conversion of the signal frequency to 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 The system operates at 100 MHz and 8 sources and 8 detectors are used, which yield 64 amplitude and 64 phase measurements. The temporal resolution of the system is 16 s, which is a pivotal feature for measuring ICG kinetics due to the fact that ICG reaches its peak concentration in about 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…MRI anatomical prior information was incorporated into the FT reconstruction algorithms, in order to improve in vivo tumor localization. This method was also exploited by Gulsen and coworkers when they built a MRI‐guided dynamic contrast‐enhanced diffuse optical tomography (DCE‐DOT) system and used it together with ICG and a MR contrast agent [Gd‐diethylenetriaminepentaacetic acid (DTPA)] for tumor characterization in a rat model. As tumors grow, they undergo necrosis and the tissue transforms from viable to necrotic.…”
Section: Emerging Technologiesmentioning
confidence: 99%